The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/7814910
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Attention Deficit Hyperactivity Disorder Symptoms in Children Who Were Treated at Emergency Service due to Unintentional Injury

Abstract: Aim Attention Deficit Hyperactivity Disorder (ADHD) is a developmental disorder characterized by severe inattention, hyperactivity, and impulsivity. This research aims to determine the frequency of ADHD symptoms in children who were treated in emergency paediatric services due to unintentional injuries. MethodThis study was carried out with children who were treated due to unintentional injuries in an Emergency Department. ADHD symptoms were evaluated using the DSM-IV-based Screening and Assessment Scale for B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…20 In a similar study, İz et al showed that ADHD symptomatology was observed in most children admitted to the emergency department for accidental injuries. 22 Children with impulsive-hyperactivity behavior have been reported to have 1.5-2 times higher risk for injury and extremity fractures. [21][22][23][24][25] In a retrospective cohort study, Guy et al assessed musculoskeletal injuries in patients aged under 17 years with ADHD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In a similar study, İz et al showed that ADHD symptomatology was observed in most children admitted to the emergency department for accidental injuries. 22 Children with impulsive-hyperactivity behavior have been reported to have 1.5-2 times higher risk for injury and extremity fractures. [21][22][23][24][25] In a retrospective cohort study, Guy et al assessed musculoskeletal injuries in patients aged under 17 years with ADHD.…”
Section: Resultsmentioning
confidence: 99%
“…22 Children with impulsive-hyperactivity behavior have been reported to have 1.5-2 times higher risk for injury and extremity fractures. [21][22][23][24][25] In a retrospective cohort study, Guy et al assessed musculoskeletal injuries in patients aged under 17 years with ADHD. In the 11-year study period, the following traumatic musculoskeletal injuries were diagnosed in patients with ADHD; sprains (27.2%), fractures (21.2%), concussions (4.5%), dislocations (2.8%), and thoracic and pelvic injuries (0.6%).…”
Section: Resultsmentioning
confidence: 99%
“… 18 On the other hand, ADHD can cause sleep-related obstructive breathing, altered pattern of sleeping, and daytime sleepiness which has a negative impact on school performance and social life. 19 21 In community studies with different cultures, mouth breathing and ADHD are observed together in 54 and 5–13% of children in different studies. 1 , 17 , 22 In the current study, 7% of the mouth-breathing children full filled the complete DSM V criteria of ADHD which accurately diagnoses ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…The rate ratio for ADHD with one or more comorbid mental health conditions versus ADHD only is 4. 19 ). Other rate ratios measuring the association between poisoning, burns, and head injuries and OCD or depression or anxiety are even lower, albeit positively significant (data not shown).…”
Section: Rates Of Injury By Adhd Status and Comorbid Mentalmentioning
confidence: 99%
“…Research has shown that ADHD is positively associated with emergency services, hospitalization, and healthcare claims for injuries [17][18][19][20][21][22]. A study involving medical claim data in the U.S. showed that for ages 0-64 years, more severe injuries (versus less severe injuries) and an increasing number of injuries were positively association with ADHD [17].…”
Section: Introductionmentioning
confidence: 99%